Increase and Change in the Pattern of Antibiotic Use in Serbia (2010-2019) - Ana Tomas; Nebojša Pavlović; Nebojša Stilinović; Olga Horvat; Milica Paut-Kusturica; Tihomir Dugandžija; Zdenko Tomić; Ana Sabo (MDPI AG, 2021)
The aim of this study was to determine and describe trends in antibiotics utilization in Serbia over a ten-year period. Data were retrieved from publicly available annual reports (2010-2019). The results were expressed as Defined Daily Dose (DDD) per 1000 inhabitants per day (DID). All calculations were performed using the DDD values for the 2020 Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) version for each year of the study, to account for the DDD changes during the study period. Antibiotics were classified using the WHO Access, Watch, Reserve (AWaRe) classification. Total utilization of antibacterials for systemic use increased from 17.25 DID in 2010 to 28.65 DID in 2019. A statistically significant increasing trend in the use of the Watch category antibiotics was observed. A tendency towards use of broad-spectrum antibiotics, apparent by a statistically significant increase in the rate of utilization of broad-spectrum macrolides, quinolones and third-generation cephalosporins vs. narrow-spectrum ones, as well as a significant increasing trend in the use of quinolones was identified. Total antibiotic utilization was found to be well above the European average. Several specific problem areas were identified, which requires further efforts to improve antibiotic prescribing. The present study provides the information needed to facilitate antibiotic stewardship in Serbia further and proposes specific interventions to optimize antibiotic use in Serbia.